2022
DOI: 10.1071/py21256
|View full text |Cite
|
Sign up to set email alerts
|

‘Look, wait, I’ll translate’: refugee women’s experiences with interpreters in healthcare in Aotearoa New Zealand

Abstract: This study aimed to explore refugee women's experiences of interpreters in healthcare in Aotearoa, New Zealand (NZ). Semi-structured interviews were conducted with nine women who arrived in NZ as refugees. Analysis involved a 'text in context' approach. An iterative and interpretive process was employed by engaging with participant accounts and field notes. The various meanings behind participants' experiences were unpacked in relation to the literature and the broader socio-cultural contexts in which these ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Allowing time for questions and listening to the consumer helped the HCP assess the understanding level of what was discussed, facilitated further discussion, and fostered trust in the HCP and the healthcare service (Pene et al, 2021). Cassim et al (2022) highlighted the importance of including whānau in discussions because some consumers may not be able to receive and process information.…”
Section: Resultsmentioning
confidence: 99%
“…Allowing time for questions and listening to the consumer helped the HCP assess the understanding level of what was discussed, facilitated further discussion, and fostered trust in the HCP and the healthcare service (Pene et al, 2021). Cassim et al (2022) highlighted the importance of including whānau in discussions because some consumers may not be able to receive and process information.…”
Section: Resultsmentioning
confidence: 99%
“…The length of stay of participants in Aotearoa prior to the studies also varied, with two studies not stating this information [ 35 , 43 ]. Three studies had an average of four and five years for women and men, respectively [ 33 , 34 , 38 ], one study was between three months to 21 years [ 40 ], one study between six months to three years [ 26 ], two studies with an average of 3.25 years [ 41 , 42 ] and another two studies between 1 and 19 years [ 36 , 37 ]. Two of the studies did not include any information of length of stay as they focused on healthcare providers [ 5 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies predominantly had women participants. Two studies focused on women only [ 36 , 37 ], two studies were women with children [ 41 , 42 ], and one study was with parents though women made up most of the participants [ 43 ]. Of the studies, four studies had a small proportion of men in the sample group [ 26 , 33 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FHBs’ dissatisfaction with and warning about harm resulting from miscommunication (theme 3) are corroborated by interviews with refugees which revealed that they were concerned about interpreters not maintaining confidentiality, not understanding medical terminology, and not speaking the same dialect [ 42 ]. Miscommunication was found to be a barrier to managing medications [ 43 ] and that it can harm refugees’ health [ 33 ]. Miscommunication concerning medical procedures resulted in perceived unsatisfactory care [ 44 ].…”
Section: Discussionmentioning
confidence: 99%